Pengembangan Bahan Ajar Guru Pada Mata Pelajaran Akhlak Kelas IV di Madrasah Diniyyah Takmiliyah Awaliyah Masjid Agung Ashliyah - Nurasyiah Nurasyiah; Taufik Rahman; Diana Sartika (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
Madrasah Diniyah Takmiliyah Awaliyah was one of the non-formal education in Indonesia, however there are several problems in learning at MDTA such as those found in moral learning at MDTA Masjid Agung Ashliyah Padang Panjang, namely teacher textbooks in teaching have not met learning objectives because the material is still limited and incomplete, the books provided by the madrasah are also still limited and teachers have not used teaching tools in the form of lesson implementation plans (RPP) in the learning process, so that the learning process is less effective and efficient. This study aims to produce a product in the form of teacher teaching materials as a guide for teachers in teaching. This study is entitled